CURRENT INFORMATION NEEDS OF PASSENGER AND FREIGHT TRANSPORTATION ENTERPRISES IN RUSSIA - Shnaider V.V.; Pipko E.G.; Petrov A.M. (Scientific Journal of Pedagogy and Economics, 2020)
he current business environment cannot exist without information flows. Information is an integral part of all structural processes of economic entities, regardless of the sphere of activity. Information dependence is a topical issue not only for economic entities, stakeholders, the state but also for the world in general. There is an obvious need for reliable and timely information. There is no doubt that information is considered the most valuable asset of the twenty-first century. Information is understood as processed and systematized quantitative or qualitative data. News about economic events, environmental disasters, social unrest around the world result in adjusting the plans and strategies of entire countries and their resident companies. To stick to the principles of responsible behavior and sustainable development, governments need reliable qualitative and quantitative data about the economic, social and environmental spheres. At the macro level, reliable information about the global political, economic, social and environmental situation contributes to effective decision making. Environmental changes force governments to develop strategies on environmental protection. Information has a wide range of users, from one individual to the entire world. Identification and analysis of information needs is a very topical issue today. To provide stakeholders with consistent and relevant information, such needs must be properly addressed and understood. For an economic entity, relevant information may produce strong economic and managerial benefits, while irrelevant information, on the other hand, may affect adversely the entity’s market value and its development perspectives.